2017
DOI: 10.1037/cou0000177
|View full text |Cite
|
Sign up to set email alerts
|

Experiencing racial microaggressions influences suicide ideation through perceived burdensomeness in African Americans.

Abstract: Racial microaggressions are a contemporary form of subtle discrimination that occur in everyday exchanges, and are associated with a variety of negative mental health outcomes, including suicide ideation. Previous work (e.g., Torres-Harding, Andrade, & Romero Diaz, 2012) has identified 6 dimensions of racial microaggressions: invisibility, criminality, low-achieving/undesirable culture, sexualization, foreigner/not belonging, and environmental invalidations. The current study examined whether the 6 dimensions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(77 citation statements)
references
References 40 publications
6
66
1
4
Order By: Relevance
“…The regularity and ambiguity of this discrepancy in perception has a detrimental impact to those on the receiving end. Hollingsworth et al (2017) used self assessments to evaluate the psychological impact of microaggressions on African American high school students, and found that frequent microag gressions were strongly associated with increased perceptions of selfburdensomeness and thoughts of suicide. Similar methodology found that the daily microaggressions experienced by children of Latino immigrants were strongly correlated with social isolation, poor health outcomes, and internal ized oppression (Ayón & Philbin, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The regularity and ambiguity of this discrepancy in perception has a detrimental impact to those on the receiving end. Hollingsworth et al (2017) used self assessments to evaluate the psychological impact of microaggressions on African American high school students, and found that frequent microag gressions were strongly associated with increased perceptions of selfburdensomeness and thoughts of suicide. Similar methodology found that the daily microaggressions experienced by children of Latino immigrants were strongly correlated with social isolation, poor health outcomes, and internal ized oppression (Ayón & Philbin, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Their research described how racial nonverbal microaggressions affected embodiment, or connectedness to one’s body, for participants from diverse racial, ethnic, and gender expression backgrounds. Similarly, Hollingsworth et al (2017) found that, for African Americans, the cumulative experiences of racial microaggressions were connected to increased feelings of being burdensome to others, leading to increased suicidal ideation.…”
Section: Counselors Of Color’s Experiencesmentioning
confidence: 96%
“…For example, a sample of 348 university students revealed that the intensity of cyberbullying is related to suicidal ideation mediated by the PB variable and symptoms of depression (Mitchell et al, 2016). Other studies involving African populations (N = 135) have noted that experiencing certain racial microaggressions -invisibility, culture of low performance or undesirability, and invalidations by the environment -are associated with suffering from higher levels of PB, which is related to higher suicidal ideation (Hollingsworth et al, 2017).…”
Section: Article In Pressmentioning
confidence: 99%